Protective Renal Effects of Atrial Natriuretic Peptide: Where Are We Now? - Choi, Marcelo Roberto; Fernández, Belisario Enrique (Frontiers in Physiology, 2021)
Atrial natriuretic peptide belongs to the family of natriuretic peptides, a system with natriuretic, diuretic, and vasodilator effects that opposes to renin-angiotensin system. In addition to its classic actions, atrial natriuretic peptide exerts a nephroprotective effect given its antioxidant and anti-inflammatory properties, turning it as a beneficial agent against acute and chronic kidney diseases. This minireview describes the most relevant aspects of atrial natriuretic peptide in the kidney, including its renal synthesis, physiological actions through specific receptors, the importance of its metabolism and its potential use in different pathological scenarios.